2021
DOI: 10.37201/req/126.2021
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for antibiotic selection for severe nosocomial infections

Abstract: Severe infection and its evolution to sepsis are becoming more prevalent every day and are among the leading causes of critical illness and mortality. Proper management is crucial to improve prognosis. This document addresses three essential points that have a significant impact on this objective: a) early recognition of patients with sepsis criteria, b) identification of those patients who suffer from an infection and have a high risk of progressing to sepsis, and c) adequate selection and optimization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 108 publications
0
31
0
Order By: Relevance
“…In this study, we found that the mortality rate in the shock group of bloodstream infection was significantly higher than that in the non-shock group, which may be related to the multiple-organ failure caused by shock, further confirming that septic shock is a major lethal factor in bloodstream infection [ 25 ]. Excessive inflammatory response and immune dysfunction can lead to lymphocyte apoptosis and increased PCT, neutrophil count, and NLR [ 26 ], which have been reported to be correlated with higher 28-day mortality in patients with septic shock [ 27 ]. In this study, PCT0h (PCT at 0 h) and PCT48h (PCT at 48 h) in the septic shock group were significantly higher than those in the non-shock group, which could be used as predictors of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the mortality rate in the shock group of bloodstream infection was significantly higher than that in the non-shock group, which may be related to the multiple-organ failure caused by shock, further confirming that septic shock is a major lethal factor in bloodstream infection [ 25 ]. Excessive inflammatory response and immune dysfunction can lead to lymphocyte apoptosis and increased PCT, neutrophil count, and NLR [ 26 ], which have been reported to be correlated with higher 28-day mortality in patients with septic shock [ 27 ]. In this study, PCT0h (PCT at 0 h) and PCT48h (PCT at 48 h) in the septic shock group were significantly higher than those in the non-shock group, which could be used as predictors of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…This agent also has activity against producers of β-lactamases from classes A and C per the Ambler classification (and also varying activity against class D, albeit not class B enzymes, i.e., metalloβ-lactamases [MLB]) [ 16 ]. It is because of its ability to have good in vitro activity—even for KPC-producing strains—that this combination is recommended in recently published guidelines on empirical treatment of patients with severe gram-negative bacilli infections [ 17 ]. CAZ/ AVI is a very good agent (>99% susceptibility) against more than 8,000 Enterobacteriaceae isolates (MIC 50 /MIC 90 , 0.12/0.25 mg/L) collected from hospitals in the United States (US) [ 18 ].…”
Section: New Beta-lactamsmentioning
confidence: 99%
“…The current criteria for Sepsis have a high specificity in the diagnosis of severe infection. But their sensitivity is lower, and there are many patients with severe infections who do not meet these criteria [9,10]. To improve our ability to has an important impact on the prognosis, and therefore contributes to the to the improvement of the clinical outcomes.…”
Section: Timing In Empirical Treatmentmentioning
confidence: 99%
“…II. Bone (osteomyelitis), endocardium (endocarditis), vitreous humor (endophthalmitis)... cases where the clinical evolution is favorable, should be considered [9,22]. It is based on the idea that most of the overall efficacy of antibiotherapy is achieved in the first days of treatment, and once a significant clinical improvement has been observed, a practically complete extinction of pathogenic bacterial inoculum has been done, and microbial regrowth and recurrence of symptoms would not occur in patients without severe immunosuppression, uncontrolled septic foci or prosthetic material with ineradicable inoculums.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation